A Middleware Perspective for Integrating Ginga-NCL Applications with the Internet of Things - Pereira, Danne Makleyston Gomes; Silva, Francisco José da Silva e; Neto, Carlos de Salles Soares; Guedes, Álan Lívio Vasconcelos (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
IoT (Internet of Things) technologies are underway. They allow the inter-connection of physical devices (also called "smart objects") that are embedded with electronics and network connectivity allowing these objects to collect and exchange data. Smart objects can be used in residential environments turning objects of everyday life (e.g. lamps, thermostats and speakers) into digital products that can emits data about its usage, location and state, can be tracked, controlled, personalized and even upgraded remotely. On the other hand, currently TV devices have extended their traditional usage by allowing applications such as web navigation, social TV and gaming. This work proposes an approach for integrating the TV with surrounding smart objects through a middleware approach, taking as its base Ginga-NCL, the Brazilian middleware for digital TV, and M-Hub, a middleware that allows the discovery, connection, communication, and data distribution of IoT smart objects. The proposed software infrastructure is evaluated in different usage scenarios that allows: (i) the TV application to modify the surrounding environment through the use of actuators, (ii) to adapt the content being presented according to the perception of the environment provided by sensors; and (iii) to provide new modes of user interaction with the TV.